2015
DOI: 10.1007/s00381-015-2702-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in retinal nerve fiber layer thickness in tuberous sclerosis complex

Abstract: Since a reduced RNFL thickness might be seen as an indicator of chronic axonal degeneration or lack of appropriate neuronal development, our results support the presence of axonal alterations in TSC and also that white matter disorganization could be much more diffuse than originally thought. Since axonal alterations directly derive from mammalian target of rapamycin (mTOR) overactivation, which occurs early during fetus development, the RNFL thinning we observed could represent one of the facets of such early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…Our results showed RFNL thinning in the superior and inferior disc sectors of subjects with TS compared with healthy controls. Our findings agree with the work of Gialloreti et al [ 4 ], who also found RNFL thinning in TS patients. However, their study did not evaluate the macular measurements.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results showed RFNL thinning in the superior and inferior disc sectors of subjects with TS compared with healthy controls. Our findings agree with the work of Gialloreti et al [ 4 ], who also found RNFL thinning in TS patients. However, their study did not evaluate the macular measurements.…”
Section: Discussionsupporting
confidence: 94%
“…Aronow et al [ 11 ] demonstrated that RAHs are more likely to coexist with subependymal astrocytomas, renal angiomyolipomas, cognitive impairment, and epilepsy, underscoring the importance of accurately identifying RAH and retinal features in TS patients. While several studies have described retinal changes associated with RAH [ 12 15 ], the quantification of RNFL and macular thickness has been rarely explored [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bildmorphologisch ist der Befund zum Teil einem transparenten Astrozytom der Neuroretina [32] ähnlich oder aber auch einem nicht kalzifizierten, retinalen astrozytären Hamartom [33]. Die erworbenen retinalen Astrozytome (ARA) sind meistens endophytisch und ragen in den Glaskörperraum hinein, allerdings erscheinen sie funduskopisch gelblich und semitransparent, sind deutlich vaskularisiert, weisen selten Verkalkungen auf und können sporadisch, unabhängig von systemischen Erkrankungen auftreten [33].…”
Section: Spezifische Okuläre Symptome Der Nf2unclassified